The Ideational, Interpersonal and Textual Meaning in Jokowi Dodo's Inauguration Speech (e-Journal of Linguistics, 2019)
Systemic Functional Linguistic offers a model of approach in analyzing discourseconcerning to reveal how language is used to negotiated meaning. Research paper, also known asresearch article presents Jokowi Dodo’s Inauguration speech in terms of Ideational, interpersonaland textual meaning. Therefore, this study aimed to explain the realization of Ideational,Interpersonal and Textual Meaning in Inauguration speech. Descriptive qualitative Researchdesign was used in this study with one Jokowi Dodo’s text speech taken as the subject ofanalysis . The findings revealed that the meanings were realized by the president’s languagechoice. Ideational meaning realized in research paper showed that the president presented hisfuture dreams in state of doing through relational process and material process with help of otherprocess types. However, Interpersonal meaning realized in the research paper showed that theresearch paper was carrying the speech role as giving information. Textual meaning was realizedthrough the use of the speech opening and giving appreciate to participants who attended inInauguration speech and also hopes to all participants. The realization of the meaning also couldgive benefit to participant and researcher in having guideline when they are giving speech inpublic area.